COMPARISON ANALYSIS OF RAILWAY BRIDGE MODUL FOR â€œIâ€ GIRDER TYPE AND â€œWARRENâ€ TRUSS TYPE - Purnomo, Dwi Agus; Utomo, Djoko Prijo; Waseso, Agung Barokah; Marindaa, Mira (Majalah Ilmiah Pengkajian Industri, 2020)
The railway bridge in Indonesia, with a width of 1067 mm, was built in 1878, so that maintenance modules are needed to repair or to replace of construction modul at regular intervals. Implementation of maintenance and repairs refers to the Minister of Transportation Regulation No. 60 of 2012. Problems were encountered in the field at the BH182 Daop 2 railway bridge in Bandung due to lowering structural strength. Therefore, it was necessary to repair the bridge module with a new bridge design. The purpose of this study is to analyse and to calculate strength of the structure and to determine effectiveness of the use of construction materials on 2 alternative bridge construction selection with the type of ?I" girder and the type of ?Warren" Truss. Design implementation method used is to utilize Midas Civil Structure software. The loading used for railway bridges is grouped into three load groups, namely the girder's self-weight, additional dead load, and live load. Additional dead load analysed is line load including bearings, while for live load is trainset load based on loading requirements. From the results of calculations between the steel bridge ?I" girder type height of 300 cm and the type of ?Warren" Truss height of 600 cm, each span of 30 m showed that those were a function of the railway bridge. It would be more effective to use the type of ?Warren? Truss structure that is quite able to withstand train traffic loads in accordance with applicable standards.